2011
DOI: 10.1007/s13361-011-0106-z
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Mass Spectrometry of Modified and Platinated Oligoribonucleotides

Abstract: Therapeutic approaches for treatment of various diseases aim at the interruption of transcription or translation. Modified oligonucleotides, such as 2′-O-methyl-and methylphosphonatederivatives, exhibit high resistance against cellular nucleases, thus rendering application for, e.g., antigene or antisense purposes possible. Other approaches are based on administration of cross-linking agents, such as cis-diamminedichloroplatinum(II) (cisplatin, DDP), which is still the most widely used anticancer drug worldwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…The output obtained by considering all possible types of fragment ions is shown in Figure 6b. In contrast to unmodified RNA, abundant fragment ions were assigned as members of the d-and z-ion series, which is in good agreement with the dissociation mechanisms of methoxymethylphosphonate [8].…”
Section: Example 2: Modified Rnasupporting
confidence: 74%
See 1 more Smart Citation
“…The output obtained by considering all possible types of fragment ions is shown in Figure 6b. In contrast to unmodified RNA, abundant fragment ions were assigned as members of the d-and z-ion series, which is in good agreement with the dissociation mechanisms of methoxymethylphosphonate [8].…”
Section: Example 2: Modified Rnasupporting
confidence: 74%
“…Cisplatin is one of the most widely used chemotherapeutic drugs and was found to form adducts with DNA, RNA, and proteins in vivo. The impact of cisplatin on the gas-phase dissociation of single-stranded DNA and RNA has been investigated extensively in the past few years [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44] Because one can predict the fragment ions produced, one can also determine the sequence of an oligonucleotide based on the mass and the fragment ions generated de novo. From the precursor mass a list of potential nucleotide compositions can be generated, and depending on the enzyme used, some limitations of compositions can be incorporated into the analysis scheme.…”
Section: Rna Modification Mapping Of Trnas and Rrnasmentioning
confidence: 99%
“…While methylphosphonate nucleic acids themselves are of interest for antisense applications, they represent a valuable instrument to study the role of specific phosphate groups in gas-phase recent years, a comprehensive armamentarium of dissociation mechanisms has been assembled, which can be applied to deciphering tandem mass spectrometric data obtained from DNA, RNA, and the many structurally altered oligonucleotide analogues. [6][7][8][9][10][11][12] …”
Section: Ta Ndem Mass Spectrometry Of Oligonucleotidesmentioning
confidence: 99%
“…Comparative analysis of 2'-O-methyl oligoribonucleotides confirmed that the 2'-hydroxyl group is not involved in the formation of the high-intensity w-ion. [9] In fact, the platinated RNA dissociates in a DNA-like manner as a result of the cisplatin moiety that destabilizes the N-glycosidic bond.…”
Section: Interaction Of Cisplatin With Single-stranded Nucleic Acidsmentioning
confidence: 99%